The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-695x2010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and enzymatic bioassays with Serjania erecta Radlk., Sapindaceae, correlated with cognitive dysfunctions

Abstract: RESUMO: "Comportamento e ensaios bioenzimáticos com Serjania erecta Radlk., sapindaceae, correlacionados com disfunções cognitivas." O objetivo deste estudo foi pesquisar o extrato bruto de Serjania erecta Radlk., Sapindaceae, e seus bioativos como preventivos ou inibidores de perda de memória em roedores, e outros fatores correlacionados com a síndrome de Alzheimer: atividade antioxidante e anticolinesterásicas, principalmente como planta adaptógena, baixa toxicidade e ação regulatória. A reversão do bloquead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The delayed development and weight loss observed in C. includens may have been related to the phenolic compounds found in the S. erecta extract, including kaempferol 28 , saponins 29 , and apigenins 28 . Phenolic compounds may cause a significant reduction in the survival and growth of insects due to the inactivation of digestive enzymes 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The delayed development and weight loss observed in C. includens may have been related to the phenolic compounds found in the S. erecta extract, including kaempferol 28 , saponins 29 , and apigenins 28 . Phenolic compounds may cause a significant reduction in the survival and growth of insects due to the inactivation of digestive enzymes 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding S. erecta , there are few reports in the literature regarding the inhibitory activity of its extracts. Broggini et al 29 showed the inhibitory effect of crude extracts of this species using thin layer chromatography. In this work, the flavonoid fraction of this extract was shown to be more selective for inhibition of acetylcholinesterase than for that of butyrylcholinesterase, while the saponin fraction showed greater inhibition of butyrylcholinesterase than of acetylcholinesterase 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract was obtained by the method described by Broggini et al (2010), with adaptations. Leaves were dried in a forced-air circulation incubator with microprocessor and air renewal (Sterilifer -SXCR 40) at 37 ± 2 °C for 48 h and ground through a Wiley mill (TE-680-Tecnal) with a 10-mesh screen.…”
Section: Plant Material Preparation and Chemical Composition Of S Ere...mentioning
confidence: 99%
“…[e.g. Serjania marginata (Périco et al 2015, Moreira et al 2019, Serjania caracasana (Silva et al 2017), and S. erecta (Castelo et al 2009, Broggini et al 2010] in mice. However, no studies have evaluated the toxicity of S. erecta in aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%